(untitled) (Eurasian Research Bulletin, 2023)
In this article, we embark on a journey through time to unravel the past, delve into the current state of affairs, and explore potential avenues for the future of the Aral Sea. From its ancient origins as a vital source of life to the stark reality of its rapid decline, we will examine the various factors that have contributed to this ecological disaster. Furthermore, we will assess the efforts undertaken to mitigate the damage and restore the Aral Sea to its former glory.